Application of Collaborative Care Model on Components of Caregiver Burden in Families of Patients with Mental Disorders - Amin Haghgoo; Mohammad Zoladl; Khairollah Nooryan; Shirali Kharamin; Soleiman Afrooghi (Golestan University of Medical Sciences, 2018)
Background: Collaborative care can be used as a component of self-care in reducing the complications of care in family caregivers of mental patients. Therefore, the present study aims to "determine the impact of the use of collaborative care model on the care burden parameters of the family of patients with mental disorders". Methods: In this clinical trial, 66 households from family caregivers of mental patients participated who were eligible for inclusion in a study in the Shahid Rajaee Hospital of Yasuj in 2014.  The samples were available and were divided into two groups of intervention (33 families) and control (33 families) based on simple random sampling. The instruments were demographic information sheet, primary needs assessment checklist, Novak's caregiver burden inventory (CBI). Collaborative care model was implemented based on the motivation, preparation, involvement and evaluation phases in the intervention group for 11 sessions. No intervention was performed for control group during this period. Data analysis was performed based on descriptive and inferential statistics (Chi-square, independent t-test, and Mann-Whitney) using SPSS V.21 with a significant level (p< 0.05). Results: The results showed that there was no significant difference in the scores of care burden between the two groups before intervention (P> 0.05); however, after implementation of the model, there was a significant difference between the mean care burden and all the components of the intervention group and the control group. (P< 0.05). Conclusion: Implementation of collaborative care model is effective in decreasing the care burden of the family of patients with mental disorders. Therefore, it is recommended using of this model in health care.